A Two-Warehouse Fuzzy Inventory Model for Deteriorating Items Under Exponentially Increasing Demand - Singh, Chandra Prakash (Journal of Global Economy, Business and Finance, 2025)
In this paper, our study is to develop an inventory policy for deteriorating items dealing with two-warehouse system owned and rented under fuzzy environment. The constant rate of deteriorating items and exponentially increasing demand pattern are considered in the present model. The owned warehouse (OW) of finite capacity and rented warehouse (RW) of large capacity of items are assumed here. Normally retailer wants to sell the inventory in RW first, inventory of RW reaches zero level due to deterioration and demand, while that of OW is depleted due to deterioration only. Both crisp and fuzzy models are developed in the proposed study. The signed distance method (SD) is used to defuzzify the total system cost of the model. Suitable illustrations for both crisp model and fuzzy model are furnished and lastly a sensitivity analysis of the optimum solution towards changes the fuzzy cost parameters are given along with few pictorial presentations discussing the observation on the outcomes of the system solution.